The Sanctuary of Hercules Victor. A renewed image in the Tiburtina landscape (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2024)
The paper explores how ordinary green maintenance in an archaeological site can contribute to an overall reinterpretation of the architectural artifact itself using as a case-study the management experience of the Sanctuary of Hercules Victor, Tivoli. The complex, located in a scenically significant position, boasts a two-thousand-year reuse that has allowed it to be preserved up to the present day. Starting from the “Progetto Strategico – Grandi Progetti Beni Culturali”, the preliminary cleaning operations of the greenery of the northern front have provided a renewed vision, particularly from the other ridge of the Aniene river, enabling us to draw a parallel with the contemporary structures of the Canevari Canal. Ancient and contemporary features are confronted again as part of an overall reinterpretation of the landscape. Keywords: Sanctuary of Hercules Victor, Tivoli, Cultural landscape, Historical palimpsest